STUDI MODEL PENGENDAPAN MENGGUNAKAN DATA SEISMIK DUA DIMENSI PADA BLOK EKSPLORASI MINYAK DAN GAS BUMI âSMâ, CEKUNGAN MAKASSAR SELATAN, SELAT MAKASSAR - , RAHMADI HIDAYAT ([Yogyakarta] : Universitas Gadjah Mada, 2012)
"SM" Block is located at Makassar Strait, as a part of South Makassar Basin (SMB) which is very potential for oil and gas exploration in Eastern Indonesia. Indication of hydrocarbon seepages within study area based on Airborne Laser Fluorescence (ALF) survei as well as gas discovery in Makassar Strait-1 prove that petroleum system is working in SMB. However, detail studies in this area is still not developed well. One of the studies which can be utilized for further discoveries of oil and gas field is study of depositional fasies using seismic facies method to maximize limited 2D seismic data and well data. Seven sequences have been extracted based on seismic facies in "SM" Block. Three fault patterns were influenced SMB, which are 2 Paleogene Rifting patterns (Taka Talu (TTFZ) and Adang (AFZ)) and West Sulawesi Fold Belt (WSFB). In contrary, northeastern-southwestern TTFZ is the only main fault pattern which were implied in "SM" Block. Interpretation of depositional facies model in Eocene (syn-rift phase) was varied from aluvial plain and aluvial fan complex, continued gradually to platform and basinal plain. In Oligocene time (post-rift phase), transgression caused deepening to marine environment with lateral variation of platform, slope, while basinal plain in "SM" Block. Early Miocene - recent interval (syn-orogenic phase), SMB experienced slightly progradation eventough in marine condition respectively. This tectonic phase was not influenced the environment of "SM" Block, which relatively stable in basinal plain.